PENGGUNAAN METODE PENELITIAN PEREMPUAN DALAM KASUS PEREMPUAN DAN KONFLIK DI TIGA KOTA - Widjajanti M Santoso (Jurnal Masyarakat dan Budaya, 2010)
Despite the abundance of social conflict research, those focusing on women issues are actually quite rare. This writing is based on a research using women’s research method to unfold the role of women in conflicted areas in the city of Poso, Maluku and Atambua. Focusing on women, and integrating it with the research method that was used, it appeared that women has played a significant role in resolving social conflict in the community. Women also played an important role in preventing sexual abused cases and other impacts of social conflict. This research served as a preliminary data for Resolution 1325 dissemination, which emphasized the special attention to women and children in any occurrence of social conflict. The main conclusion of this research is that women’s knowledge needs to be elaborated; therefore greater public can understand the significant role of women in conflict areas. Although concurrently becomes victims at most conflict occurrence, women also has significant role in resolving conflict at community level. Keywords: women’s role, social conflict, women’s research method